KOMPETENSI RÃ‰LIGIUS BERKARAKTER ÅªLÅªL â€˜ILMI BAGI GURU PENDIDIKAN AGAMA ISLAM - Nurti Budiyanti; Asep Abdul Aziz; Aan Hasanah (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2021)
The decline in the quality of education in Indonesia is inseparable from the decline in the quality of teachers. Looking at this kind of reality, surely a teacher is required to keep improving his competence well. The purpose of this study is to formulate competencies that must be possessed by PAI teachers, namely religious competence, this competence needs to be developed to carry out their educational duties. Religious competence shows the commitment of PAI teachers as the main criterion so that all problems of educational behavior are faced, considered, solved and placed in an Islamic perspective. This research design uses a qualitative-descriptive approach. The research method used is literature study (literature study). The results of this study indicate that; first, the concept of religious competence with lÅ«l 'ilmi character as a solution to improve the quality of PAI teachers. The word lÅ«l 'ilmi is taken in the concept of the Qur'an which means a person who has knowledge based on reality, has broad insight, his intelligence is able to reach makrifat, and his heart is steadfast in monotheism because he has the level of khayyah like the scholars. Second, religious competence with lÅ«l 'ilmi character has distinctive characteristics that are different from the others, namely that this character has IlÄhiyyah, spiritual and spiritual nuances. This feature covers 6 domains, namely the cognitive domain, the affective domain, the psychomotor domain, the social domain, the ethical realm and the spiritual realm. In conclusion, the main key to the character of lÅ«l 'ilmi for PAI teachers is to create a strong khÄyyah against his Rabb, as the cause of the knowledge he has.